Migraine in children population - systemic review - Wieteska, Małgorzata; Maj, Dominik; Gendek, Karolina; Bąk, Weronika; Chrościńska-Krawczyk, Magdalena (Journal of Education, Health and Sport, 2022)
Introduction and objective: Migraine constitutes the main reason for acute and recurrent headache among children globally. It is a primary headache syndrome that affects from 3 up to 10% of paediatric population. The frequency of migraine increases with age up to puberty. The aim of this study is to systemize recent knowledge about migraine in children. The information used in the presented analysis was obtained by searching academic research databases: Google Scholar and PubMed. An abbreviated description of the state of knowledge: The exact pathogenesis of migraine remains unknown, but involvement of nervous system, cardiovascular system, genetic predisposition and environmental factors are considered in the development of disease. Symptoms of migraine vary between individuals and can be wide-ranging. They may resemble disorders such as tension headache, cluster headache, epilepsy, brain tumour or ischemic stroke. The diagnostic process is based on anamnesis, and may therefore be challenging in children because of difficulties related to communication. Symptom-relieving therapy of migraine is well-established in contrast to pharmacological prophylactic treatment which is not sufficiently evidence-based. Summary: Migraine remains a global problem in the paediatric population. The condition is associated not only with physical pain, but also it leads to many long-term complications such as emotional problems and social disruption. Lack of safe and effective preventive medical therapies is a driving factor to improve trials of migraine treatment in the future.